Poaceae Pollen from Southern Brazil: Distinguishing Grasslands (Campos) from Forests by Analyzing a Diverse Range of Poaceae Species - Radaeski, Jefferson N.; Bauermann, Soraia G.; Pereira, Antonio B. (Frontiers in Plant Science, 2016)
This aim of this study was to distinguish grasslands from forests in southern Brazil by analyzing Poaceae pollen grains. Through light microscopy analysis, we measured the size of the pollen grain, pore, and annulus from 68 species of Rio Grande do Sul. Measurements were recorded of 10 forest species and 58 grassland species, representing all tribes of the Poaceae in Rio Grande do Sul. We measured the polar, equatorial, pore, and annulus diameter. Results of statistical tests showed that arboreous forest species have larger pollen grain sizes than grassland and herbaceous forest species, and in particular there are strongly significant differences between arboreous and grassland species. Discriminant analysis identified three distinct groups representing each vegetation type. Through the pollen measurements we established three pollen types: larger grains (>46 µm), from the Bambuseae pollen type, medium-sized grains (46–22µm), from herbaceous pollen type, and small grains (<22 µm), from grassland pollen type. The results of our compiled Poaceae pollen dataset may be applied to the fossil pollen of Quaternary sediments.